Betablockers do not increase efficacy of band ligation in primary prophylaxis but they improve survival in secondary prophylaxis of variceal bleeding. Issue 7 (1st February 2018) - Pfisterer, N.; Dexheimer, C.; Fuchs, E.‐M.; Bucsics, T.; Schwabl, P.; Mandorfer, M.; Gessl, I.; Sandrieser, L.; Baumann, L.; Riedl, F.; Scheiner, B.; Pachofszky, T.; et al.
Summary: Background: Endoscopic band ligation (EBL) is used for primary (PP) and secondary prophylaxis (SP) of variceal bleeding. Current guidelines recommend combined use of non‐selective beta‐blockers (NSBBs) and EBL for SP, while in PP either NSBB or EBL should be used. Aim: To assess (re‐)bleeding rates and mortality in cirrhotic patients receiving EBL for PP or SP for variceal bleeding. Methods: (Re‐)bleeding rates and mortality were retrospectively assessed with and without concomitant NSBB therapy after first EBL in PP and SP. Results: Seven hundred and sixty‐six patients with oesophageal varices underwent EBL from 01/2005 to 06/2015. Among the 284 patients undergoing EBL for PP, n = 101 (35.6%) received EBL only, while n = 180 (63.4%) received EBL + NSBBs. In 482 patients on SP, n = 163 (33.8%) received EBL only, while n = 299 (62%) received EBL + NSBBs. In PP, concomitant NSBB therapy neither decreased bleeding rates (log‐rank: P = 0.353) nor mortality (log‐rank: P = 0.497) as compared to EBL alone. In SP, similar re‐bleeding rates were documented in EBL + NSBB vs EBL alone (log‐rank: P = 0.247). However, EBL + NSBB resulted in a significantly lower mortality rate (log‐rank: P <0.001). A decreased risk of death with EBL + NSBB in SP (hazard ratio, HR: 0.50; P <0.001) but not of rebleeding, transplantation or further decompensation was confirmed by competing risk analysis. Overall NSBB intake reduced 6‐months mortality (HR: 0.53, P = 0.008) in SP, which was most pronounced in patients without severe/refractory ascites (HR: 0.37; P = 0.001) but not observed in patients with severe/refractory ascites (HR: 0.80; P = 0.567). Conclusions: EBL alone seems sufficient for PP of variceal bleeding. In SP, the addition of NSBB to EBL was associated with an improved survival within the first 6 months after EBL. Abstract : Linked Content This article is linked to Bosch and Berzigotti and Pfisterer et al papers. To view these articles visithttps://doi.org/10.1111/apt.14546 andhttps://doi.org/10.1111/apt.14581 .